Strategi Pengembangan Kompetensi Pedagogik Guru Pendidikan Agama Islam dalam Meningkatkan Efektivitas Pembelajaran - Anae Layla Rahmania; Afiful Ikhwan; Devid Dwi Erwahyudin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in the formation of students' religious character at SDIT Nurul Iman Purwantoro. The research method used a qualitative approach with in-depth interviews with PAI teachers and the principal. The results showed that PAI teachers have very adequate pedagogical competence, characterized by the ability to understand the uniqueness of student learning styles, design differentiated learning, and integrate PAI with other subjects. The principal applies a collaborative-humanist leadership style that empowers teachers and builds a religious school culture. Supporting factors for the formation of religious character include teacher role models, a conducive school environment, structured religious programs, adequate facilities, and synergy with parents. Meanwhile, inhibiting factors include a lack of consistency in the application of values, external environmental influences, and limited internal awareness of students. This study concludes that the pedagogical competence of PAI teachers and the collaborative leadership of the principal contribute significantly to the quality of PAI learning and the formation of students' religious character.